Pendekatan Hermeneutik terhadap Alat Bukti Sumpah dalam Peradilan Islam - Zahwah Aulia Nafisya; Abdul Halim Talil; Zulhas’ari Mustafa (Media Hukum Indonesia (MHI), 2025)
An oath is one of the recognized forms of evidence in the Islamic judicial system and possesses distinctive characteristics as it integrates legal, moral, and religious dimensions. In practice, oaths are often positioned as a last resort when other forms of evidence are insufficient, giving rise to debates concerning legal certainty and substantive justice. This article aims to examine the concept and legal standing of oaths as evidentiary instruments in Islamic courts and to analyze their meaning and function through a hermeneutical approach. This study employs a library research method with normative and sociological approaches, drawing on classical fiqh literature, scholarly journals, and previous studies. The findings indicate that an oath functions not merely as a formal evidentiary tool but also as a moral mechanism that binds individuals to honesty and spiritual responsibility. The hermeneutical approach enables a more contextual understanding of oaths by considering social contexts, the objectives of Islamic law (maqÄá¹£id al-sharÄ«â€˜ah), and the dynamics of modern society. The implications of this approach emphasize that truth and justice in Islamic legal proof cannot be achieved solely through formal procedural mechanisms, but must also accommodate substantive justice and social relevance. Thus, the hermeneutical approach plays a crucial role in maintaining the relevance, justice, and humane application of oaths in contemporary Islamic adjudication.